ChemInform Abstract: Glycosmisines A and B: Isolation of Two New Carbazole—Indole‐Type Dimeric Alkaloids from Glycosmis pentaphylla and an Evaluation of Their Antiproliferative Activities. Issue 44 (15th October 2015) - Chen, Yu; Tang, Chu; Wu, Yi; Mo, Shasha; Wang, Sha; Yang, Guangzhong; Mei, Zhinan
Abstract Biological tests reveal significant cytotoxicity and an apoptosis inducing effect of the newly isolated compounds (I) and (II).